Impact of Motor-Cognitive Interventions on Selected Gait and Balance Outcomes in Older Adults: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Teraz, Kaja; Šlosar, Luka; Paravlić, Armin H.; de Bruin, Eling D.; Marusic, Uros (Frontiers in Psychology, 2022)
Background: Efficient performance of most daily activities requires simultaneous execution of motor and cognitive tasks. To mitigate age-related functional decline, various combinations of motor-cognitive training showed promising results. This systematic review evaluated the efficacy of motor-cognitive training interventions on functional outcomes in healthy and diseased older adult populations. Methods: Six online academic databases were used to retrieve eligible RCTs up to April 2021, following PRISMA guidelines and PICO criteria. A random-effects model was used for all meta-analyses performed on single- and dual-task gait speed, the Timed Up and Go Test (TUG), and Berg Balance Scale (BBS). Effect size (ES) was calculated as Hedges' g and interpreted as: trivial: <0.20, small: 0.20–0.50, moderate: 0.50–0.80, or large: >0.80. Results: From 2546 records retrieved, 95 RCTs were included for meta-analysis (n = 5587 participants; 64.7 – 86.9 years; from which n = 3746 healthy and n = 1841 diseased participants). The motor-cognitive interventions varied between types of training (e.g., sequential, simultaneous with additional or incorporated cognitive task) and target populations (healthy and diseased older adults). The results showed that cognitive-motor intervention can improve gait speed under single-task conditions (small ES=0.37, P<0.001). The effect of intervention was moderated by type of control group (Q=16.332, P<0.001): passive (moderate ES=1.00, P=0.008) vs. active controls (trivial ES=0.11, P=0.204). No significant effect was found for dual-task walking outcomes (P=0.135). Motor-cognitive intervention had a positive effect on TUG (small ES=0.43, P<0.001), where the effect of intervention was moderated by control group [passive (moderate ES=0.72, P<0.001) vs. active (small ES=0.24, P=0.002)] and by the type of the intervention [additional (small ES=0.62, P=0.014) vs. incorporated (small ES=0.41, P<0.001) vs. sequential (trivial ES=0.10, P=0.393)]. Finally, BBS scores were positively affected by motor-cognitive interventions (small ES=0.50, P<0.001) with however no significant differences between healthy and diseased populations (P=0.532), type of control group (P=0.205) or intervention modality (P=0.489). Conclusions: This study provides evidence for the effectiveness of various types of motor-cognitive interventions on performance-based measures of functional mobility in healthy and diseased older adults. Due to substantial heterogeneity and the current limited availability of different types of interventions, conclusions should be interpreted with caution.